Impact of Distance of Farming: A Test of Von Thunen's Model - Sharma, Dharani Kumar (Himalayan Review, 2011)
Available with fulltext. Key Words: Von Thunen's Model; Crop location; Cropping identity; Modern technology The Himalayan Review Nepal Geographical Society Vol. XXXI 2000 Page: 95-106 Uploaded date: 5 June, 2011